Central corneal thickness measurement by optical coherence tomography after Nd: YAG capsulotomy in patients with posterior capsule opacity - Wróblewska-Czajka, Ewa; Wylęgała, Edward (Klinika Oczna / Acta Ophthalmologica Polonica, 2008)
Purpose: Opacification of the posterior capsule remains the most frequent complication of cataract-intraocular lens surgery. Nd: YAG laser capsulotomy is actually the most common procedure performed to remove the posterior capsule opacification. YAG laser secondary posterior capsulotomy can be associated with significant complications. Possible problems include among others, corneal oedema. Our study has to determine whether the neodymium:yttrium-aluminium-garnet (Nd: YAG) capsulotomy performed in postoperative posterior capsule opacification, has an impact on corneal thickness measured by means of the optical coherence tomography. Material and methods: 55 patients (43 females and 12 males), who underwent Nd: YAG capsulotomy in posterior capsule opacification, were enrolled to the study. Mean age was 65.1 years (range 23-87). Patients were examined before and one day, week, month, three months and six months after Nd: YAG capsulotomy. Central corneal thickness was measured with use of OCT, anterior chamber depth with OCT, endothelial cell density was estimated with specular microscopy. Besides, slit lamp examination, including fundus examination, and intraocular pressure measurement were performed. Visual function was assessed in terms of best corrected distance visual acuity by means of EDTRS type charts. Median of the total laser power and single impact laser power and count of impacts were determined. In all cases medical history was taken and analyzed. Results: Statistically, significant changes of central corneal thickness at one day, week, month and three months after capsulotomy were observed. Highest relative percentage change at first day (1.9) was noted. Statistically significant correlation between central corneal thickness change and total laser power and single impact laser power was found in patients 1 month and 3 months after treatment. Conclusions: 1. Only temporary central corneal thickness increase was observed as assessed by means of OCT. 2. Nd: YAG capsulotomy should be performed with the minimal possible energy delivered to the eye.